2015
DOI: 10.1016/j.scitotenv.2015.08.095
|View full text |Cite
|
Sign up to set email alerts
|

Adapting SWAT hillslope erosion model to predict sediment concentrations and yields in large Basins

Abstract: The Soil and Water Assessment Tool (SWAT) is used worldwide for water quality assessment and planning. This paper aimed to assess and adapt SWAT hillslope sediment yield model (Modified Universal Soil Loss Equation, MUSLE) for applications in large basins, i.e. when spatial data is coarse and model units are large; and to develop a robust sediment calibration method for large regions. The Upper Danube Basin (132,000km(2)) was used as case study representative of large European Basins. The MUSLE was modified to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(49 citation statements)
references
References 66 publications
0
42
0
2
Order By: Relevance
“…Choosing a constant hillslope length of 50 m (L3) however was a good second alternative to be considered when DEM resolution is of 25 m or coarser, especially if the DEM accuracy is low. Furthermore, given the importance of hillslope length on sediment outputs reported in literature (Chaplot, 2014;Zhang et al, 2014) the impact of hillslope length on sediment predictions was explored in Vigiak et al (2015), in a study that confirmed the suitability of L2 method for prediction of sediment yields.…”
Section: Discussionmentioning
confidence: 99%
“…Choosing a constant hillslope length of 50 m (L3) however was a good second alternative to be considered when DEM resolution is of 25 m or coarser, especially if the DEM accuracy is low. Furthermore, given the importance of hillslope length on sediment outputs reported in literature (Chaplot, 2014;Zhang et al, 2014) the impact of hillslope length on sediment predictions was explored in Vigiak et al (2015), in a study that confirmed the suitability of L2 method for prediction of sediment yields.…”
Section: Discussionmentioning
confidence: 99%
“…The SWAT model assumes that HRUs would represent hillslopes, where sheet and rill erosion are the dominant sediment sources and hillslope deposition is the main sink. In reality, HRUs may extend above the sheet and rill erosion or hillslope deposition (Vigiak, Malagó, Bouraoui, Vanmaercke, & Poesen, 2015), and SY may exceed gross erosion when other sources may contribute, such as gully erosion or landslides (de Vente & Poesen, 2005;Vigiak et al, 2015). In this case, the soil erodibility factor (USLE_K) in the SWAT model may increase to reflect the effect of gully erosion and landslides on SY (Awulachew, Smahktin, Molden, & Peden, 2012).…”
Section: Impact Of Alternative Land Management Scenariosmentioning
confidence: 99%
“…These studies aimed mainly at simulating streamflow (9 studies), secondarily streamflow, sediments and nutrients (3) and finally only streamflow and sediments (1), using 2 to 13 (mean 5) sub-basins nested in meso to macroscale basins situated in North America (8), Asia (2), South America (1), Africa (1) and Oceania (1). A few studies also evaluated other approaches to calibration LIEW, 2010;VIGIAK et al, 2015) and analysis of uncertainties LIAN, 2013;ZHANG et al, 2015b), associated with the multi-site calibration of nested basins.…”
Section: Introductionmentioning
confidence: 99%
“…Only 4 of the studies on multi-site calibration described above have reservoirs within their drainage area, and only Vigiak et al (2015) calibrated their sedimentological parameters without showing details on the hydrological calibration. Considering only simple calibration, many studies with SWAT were performed in basins with the presence of reservoirs, some evaluating the hydrological effect GARBRECHT;ARNOLD, 2003;LINO et al, 2009;WAGNER et al, 2011;ZHANG et al, 2012), sedimentological effect (MISHRA; FROEBRICH; and water quality effect (ZHANG et al, 2011) of these structures.…”
Section: Introductionmentioning
confidence: 99%